Kepemimpinan Pelayan dalam Membangun Lifestyle Spiritual Generasi Digital - Joni Manumpak Parulian Gultom; Martina Novalina; Didimus Sutanto B Prasetya (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2022)
The virtual world affects the growth of the spiritual lifestyle of the digital generation. The digital era is in a different quality of church leadership. A breakthrough in servant leadership by looking at Jesus' leadership is very significant. This article raises servant leadership as a solution to building a digital generation lifestyle. The question is; what is Servant Leadership in the Bible? How is the practice? And what strategies are used in developing a digital generation lifestyle? The objectives of the research are [1] to describe the biblical notion of servant leadership, [2] to explain the practice of leadership, and [3] to formulate strategies for developing a digital generation lifestyle. The research method is descriptive and qualitative. Servant leadership is [1] based on empathy, communication, and adaptability in small groups. [2] Passionate non-judgmental spirituality, and good verbal communication. [3] The strategy of forming a digital generation lifestyle with the capacity of the gift of the Holy Spirit, actions to become a beloved leader, and building high integrity. Research contributions; [1] pastoral team in serving the digital generation, [2] reference sources in the practice of spiritual ministry,[3] for prospective pastors and students from theological schools who are prepared to become church leaders.AbstrakDunia virtual telah mempengaruhi pertumbuhan lifestyle rohani gene-rasi digital. Generasi digital berada dalam kualitas kepemimpinan gereja yang berbeda.Terobosan baru dalam kepemimpinan pelayan dengan melihat model kepemimpinan Yesus sangat penting. Artikel ini mengangkat kepemimpinan pelayan sebagai solusi membangun lifestyle generasi digital. Pertanyaannya; apakah yang dimaksud Kepemimpinan Pelayan dalam Injil? Bagaimana praktik-nya? Serta strategi apakah yang digunakan dalam membangun lifestyle generasi digital? Tujuan dari penelitian [1] Menjabarkan pengertian kepemimpinan pela-yan yang Alkitabiah, [2] Menjelaskan praktek dalam kepemimpinan tersebut, [3] Merumuskan strategi dalam pembangunan lifestyle generasi digital. Metode pe-nelitian dengan kualitatif deskriptif. Hasil nya kepemimpinan pelayan[1] menda-sarkan atas empati, komunikasi dan adaptif dalam kelompok kecil. [2] Spiritua-litas bergairah tanpa menghakimi, dan komunikasi verbal yang baik. [3] Strategi pembentukan lifestyle generasi digital  dengan kapasitas karunia Roh Kudus, tindakan untuk menjadi pemimpin dicintai, serta membangun integritas tinggi. Kontribusi penelitian; [1] team penggembalaan dalam melayani generasi digital, [2] Sumber referensi dalam praktek pelayanan rohani,[3] untuk calon pendeta dan mahasiswa dari sekolah teologi yang dipersiapkan menjadi pemimpin gereja